Steve Biko : decolonial meditations of Black consciousness - Sithole, Tendayi (Critical Africana studies., 2016)
Moving away from the domain of idolization and veneration, Tendayi Sithole situates Steve Biko within the existential repertoire of blackness as a site of subjectivity and not the object of study. Through an exploration of Biko's meditations, Sithole introduces Biko to readers as a decolonial philosopher, someone more than just a biographical subject.